POTENCIAL REPRODUTIVO DE ADULTOS DE CHRYSOPERLA RAIMUNDOI FREITAS & PENNY (NEUROPTERA: CHRYSOPIDAE) EM FUNÇÃO DA ALIMENTAÇÃO LARVAL - Pessoa, L.g.a. [UNESP]; Freitas, S. De [UNESP]; Gardim, S.; Rodrigues, K.c. (Instituto Biológico, 2024)
This work was carried out to evaluate the effect of different larval diets on the reproductive potential of Chrysoperla raimundoi. Larvae collected from insects of the third offspring rearing in the laboratory were fed with Sitotroga cerealella and Diatraea saccharalis eggs. After emergence, the adults were separated in couples and were kept in cages where they received food based on beer yeast and honey. Evaluatons were made of the period of pre-oviposition, the daily and total oviposition and also the viability of the eggs produced by these insects. With these parameters, there was elaborated an index which considers the total oviposition (TO), the mean eggs viability (MEV) and the oviposition period (OP) for estimating the reproductive potential. The two diets studied did not promote differences on the parameters evaluated. The larval food consisting of S. cerealella and D. saccharalis eggs did not affect the reproductive potential of C. raimundoi.

Procurou-se avaliar o efeito de diferentes dietas larvais sobre o potencial reprodutivo de Chrysoperla raimundoi. Larvas oriundas de insetos de terceira geração multiplicados em laboratório foram alimentadas com ovos de Sitotroga cerealella e Diatraea saccharalis. Após a emergência, os adultos foram separados em casais e mantidos em gaiolas de PVC onde receberam alimento a base de lêvedo de cerveja e mel. Foi avaliado o período de pré-oviposição, a oviposição diária e total bem como, a viabilidade dos ovos produzidos por esses insetos. Com esses parâmetros, elaborouse um índice (potencial reprodutivo - PR) que leva em consideração a oviposição total (OT), a viabilidade média dos ovos (VMO) e o período de oviposição (PO). As duas dietas estudadas não promoveram diferenças significativas sobre os parâmetros avaliados. A alimentação larval composta de ovos de S. cerealella e D. saccharalis não afeta o potencial reprodutivo de C. raimundoi.
CHRYSOPERLA RAIMUNDOI FREITAS & PENNY (NEUROPTERA: CHRYSOPIDAE) ADULT REPRODUCTIVE POTENTIAL IN FUNCTION OF THE LARVAL ALIMENTATION
Keywords: Lacewings; Chrysoperla raimundoi; reproductive potential; Sitotroga cerealella; Diatraea saccharalis.; Crisopídeos; Chrysoperla raimundoi; potencial reprodutivo; Sitotroga cerealella; Diatraea saccharalis.